Hindrances to Mindfulness: Development and Validation of a Self-Report Measures for Young Adults (Journal of Asian Development Studies, 2025)
Meditation is known to support well-being, yet the factors hindering regular practice remain underexplored. Addressing this gap, the Hindrances to Mindfulness Scale (HMS) was developed in Urdu as a reliable, psychometrically robust tool for assessing barriers to mindfulness. Convergent validity was assessed using the Urdu-translated version of The Fears and Resistance to Mindfulness Scale. In this study, scale items were developed from a literature review, traditional Buddhist frameworks on hindrances to mindfulness, and input from a focus group of 30 young adults. Five content experts reviewed the Initial 41-item pool for clarity, relevance and comprehensibility. Following Lynn's (1986) criteria, items with an I-CVI ≥ 0.78 were considered acceptable and thus included in the final scale. A pilot study with 60 young adults confirmed the normality of the items using the Kolmogorov–Smirnov test. Exploratory Factor Analysis (EFA) (N = 350; 180 males, 170 females) using Varimax rotation identified a three-factor structure—cognitive, emotional and motivational hindrance—explaining 45.01% of the total variance, indicating a well-fitting model. Confirmatory Factor Analysis (CFA) (N = 500; n = 250 males, n = 250 females) yield a refined 26 item model demonstrated strong fit indices: χ²(296) = 528.2, p < .001; χ²/df = 1.78; RMSEA = .04; GFI = .91; CFI = .96; TLI = .96. While a non-significant chi-square is ideal, the overall fit indices suggest the model is robust. Convergent validity was assessed using the Urdu translation of the fears and resistance to mindfulness scale (Naeem & Naz, 2025), with the HMS demonstrating robust convergent validity. The final scale and its subscales exhibited good reliability and strong validity, confirming the hindrance to mindfulness scale as a psychometrically sound tool for studying factors that impede mindfulness.